Ionic‐Liquid Induced Morphology Tuning of PEDOT:PSS for High‐Performance Organic Electrochemical Transistors. (3rd October 2021) - Wu, Xihu; Stephen, Meera; Hidalgo, Tania C.; Salim, Teddy; Surgailis, Jokubas; Surendran, Abhijith; Su, Xiaoqian; Li, Ting; Inal, Sahika; Leong, Wei Lin
Abstract: The ability to operate in aqueous environments makes poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate), PEDOT:PSS, based organic electrochemical transistors (OECTs) excellent candidates for a variety of biological applications. Current research in PEDOT:PSS based OECTs is primarily focused on improving the conductivity of PEDOT:PSS film to achieve high transconductance ( g m ). The improved conductivity and electronic transport are attributed to the formation of enlarged PEDOT‐rich domains and shorter PEDOT stacking, but such a change in morphology sacrifices the ionic transport and, therefore, the doping/de‐doping process. Additionally, little is known about the effect of such morphology changes on the gate bias that makes the maximum g m ( V G P e a k ), threshold voltage ( V T ), and transient behavior of PEDOT:PSS based OECTs. Here, the molecular packing and nanostructure of PEDOT:PSS films are tuned using ionic liquids as additives, namely, 1‐Ethyl‐3‐methylimidazolium (EMIM) as cation and anions of chloride (Cl), trifluoromethanesulfonate (OTF), bis(trifluoromethylsulfonyl)imide (TFSI), and tricyanomethanide (TCM). It is demonstrated that an optimal morphology is realized using EMIM OTF ionic liquids that generate smaller fibril‐like PEDOT‐rich domains with relatively loose structures. Such optimal morphology improves ion accessibility, lowering the gate bias required to completely de‐dope the channel, and thus enabling to achieve high transconductance, fast transient response, and at lower gate bias window simultaneously. Abstract : A series of morphology modulation on poly(3, 4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) using a library of ionic liquids as additives is carried out. It is demonstrated that an optimal morphology is realized using EMIM OTF ionic liquids that generate smaller fibril‐like PEDOT‐rich domains with relatively loose structures. Such optimal morphology improves ion accessibility and thus enabling high transconductance, fast transient response, and lower gate bias window simultaneously.